NAHDLATUL ULAMA AND THE TRILOGY OF BROTHERHOOD - Muluk, Muchamad Saiful; Tambunan, Rika Wahyuni; Suryanto, Ardiansyah Bagus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
Digital technology’s advances are not fully profitable for mankind, but have led to the phenomenon of destructive social change which has changed the mindset and behavior of mankind throughout the world in personal, national and state life. This requires a solution which is a common basic principle in interacting with each other in the digital era. This research looks at the historical role of Nahdlatul Ulama (NU) in responding to all social changes that have occurred in realizing peace in the world and reimplementing the spirit of the trilogy of brotherhood (ukhuwah islamiyyah, ukhuwah wathaniyyah, and ukhuwah basyariyyah/insaniyyah) initiated by KH. Ahmad Shiddiq in digital life. This research was conducted by using a literature study approach in gathering data and information, then analyzed and concluded. The results of the study show that there is NU's strong determination and commitment to maintain the world peace through its religious leaders, and the relevance of implementing the ukhuwah trilogy as a basis for thinking, acting and behaving in interactive relationships in the digital era to create world peace.